2014
DOI: 10.1111/petr.12340
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of BK virus‐associated nephropathy with CMX001 after kidney transplantation in a young child

Abstract: NC, with renal failure secondary to bilateral dysplastic kidneys, received an LRD renal transplant (tx) at 17 months of age. Her early post-tx course was complicated by persistently elevated blood polyoma BK virus DNA loads. A protocol biopsy at six months post-transplant revealed BKVAN. Blood viral loads did not respond to decreased immunosuppression or treatment with ciprofloxacin and leflunomide. Six months post-tx, her serum creatinine began to rise and we sought experimental therapy to prevent the loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…The advantage of CMX001 is its potency against all DNA viruses with no reported nephrotoxicity and ease of oral administration . Reisman et al . reported its successful use in a paediatric RTR with BKVN …”
Section: Treatment Of Bk Virus Nephropathymentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of CMX001 is its potency against all DNA viruses with no reported nephrotoxicity and ease of oral administration . Reisman et al . reported its successful use in a paediatric RTR with BKVN …”
Section: Treatment Of Bk Virus Nephropathymentioning
confidence: 99%
“…The advantage of CMX001 is its potency against all DNA viruses with no reported nephrotoxicity and ease of oral administration. 55 Reisman et al 56 reported its successful use in a paediatric RTR with BKVN. 56 Papadopoulou et al 57 have reported developing virusspecific T lymphocytes (VST) from the donor that can recognize antigens found in five common viruses encountered by immunosuppressed hosts (viz.…”
Section: Potent Immunosuppression Heralds Viral Replicationmentioning
confidence: 99%
“…After a 36‐week treatment course, BK viral load levels declined, although remained detectable. Epstein‐Barr virus (EBV) became undetectable, and renal function improved to baseline, remaining stable for a further 2‐year follow‐up, with no serious drug related adverse effects observed . In 2015, a further report showed stabilisation of renal function and resolution of viraemia in a HSCT recipient with biopsy‐proven BKVN .…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Invitro study showed that brincidofovir can inhibit BK virus replication, protein expression and production of new virion in human urothelial cell with high cellular absorption less toxicity (63). Some case reports demonstrated the efficacy of brincidofovir in BK-VAN (64,65). Recently, the data on brincidofovir treatment of cytomegalovirus (CMV) infection has been presented (66,67).…”
Section: Future Directionmentioning
confidence: 99%